ANALISIS PENGENDALIAN PERSEDIAAN BERAS PADA UD BINTANG USAHA DI KECAMATAN MUAI KABUPATEN KUTAI KARTANEGARA - -, Agus Setiawan (EKONOMIA, 2014)
The purpose of this study was to determine the number of packs of 25 kg rice stocks are the most economical in the message whenever the rice to be done by UD Star Enterprises in Sub Muai and to determine the reorder point and order supplies beraskemasan frequency of 25 kg which should be done by UD Star Enterprises in Muai Subdistrict. The analytical tool used in this research is a method of EOQ (Economic Order Quantity) is the calculation to obtain the number of bookings that can minimize the total cost of inventory. As an indicator of the optimum is not reached the point where the amount of packaging supplies 25 kg of rice after using the EOQ calculation is smaller than the amount of packaging supplies 25 kg of rice supplies in the District Business Star UD Muai, then the hypothesis is accepted. Conversely if it is optimum then the hypothesis is rejected.